Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Get immediate and reliable answers to your questions from a community of experienced experts on our platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
Let's go through the solution step-by-step:
1. Identify the translation vector:
- The original coordinates for point [tex]\( C \)[/tex] are [tex]\( (2, 4) \)[/tex].
- The new coordinates for point [tex]\( C \)[/tex] after the translation are [tex]\( (3, 2) \)[/tex].
So, the translation vector [tex]\(\vec{T}\)[/tex] is calculated by:
[tex]\[ \vec{T} = (C' - C) = (3 - 2, 2 - 4) = (1, -2) \][/tex]
2. Apply the translation vector to point [tex]\( A \)[/tex] (original coordinates [tex]\( (1, 1) \)[/tex]):
- Using the translation vector [tex]\(\vec{T}\)[/tex]:
[tex]\[ A' = A + \vec{T} = (1, 1) + (1, -2) = (1 + 1, 1 - 2) = (2, -1) \][/tex]
3. Apply the translation vector to point [tex]\( R \)[/tex] (original coordinates [tex]\( (3, 0) \)[/tex]):
- Again, using the translation vector [tex]\(\vec{T}\)[/tex]:
[tex]\[ R' = R + \vec{T} = (3, 0) + (1, -2) = (3 + 1, 0 - 2) = (4, -2) \][/tex]
4. Verification with given options:
- Comparing the new coordinates:
- For [tex]\( A' \)[/tex]: [tex]\( (2, -1) \)[/tex]
- For [tex]\( R' \)[/tex]: [tex]\( (4, -2) \)[/tex]
These coordinates match the third given option:
[tex]\[ A' = (2, -1) \quad \text{and} \quad R' = (4, -2). \][/tex]
Therefore, the correct option is:
[tex]\[ \boxed{3} \][/tex]
1. Identify the translation vector:
- The original coordinates for point [tex]\( C \)[/tex] are [tex]\( (2, 4) \)[/tex].
- The new coordinates for point [tex]\( C \)[/tex] after the translation are [tex]\( (3, 2) \)[/tex].
So, the translation vector [tex]\(\vec{T}\)[/tex] is calculated by:
[tex]\[ \vec{T} = (C' - C) = (3 - 2, 2 - 4) = (1, -2) \][/tex]
2. Apply the translation vector to point [tex]\( A \)[/tex] (original coordinates [tex]\( (1, 1) \)[/tex]):
- Using the translation vector [tex]\(\vec{T}\)[/tex]:
[tex]\[ A' = A + \vec{T} = (1, 1) + (1, -2) = (1 + 1, 1 - 2) = (2, -1) \][/tex]
3. Apply the translation vector to point [tex]\( R \)[/tex] (original coordinates [tex]\( (3, 0) \)[/tex]):
- Again, using the translation vector [tex]\(\vec{T}\)[/tex]:
[tex]\[ R' = R + \vec{T} = (3, 0) + (1, -2) = (3 + 1, 0 - 2) = (4, -2) \][/tex]
4. Verification with given options:
- Comparing the new coordinates:
- For [tex]\( A' \)[/tex]: [tex]\( (2, -1) \)[/tex]
- For [tex]\( R' \)[/tex]: [tex]\( (4, -2) \)[/tex]
These coordinates match the third given option:
[tex]\[ A' = (2, -1) \quad \text{and} \quad R' = (4, -2). \][/tex]
Therefore, the correct option is:
[tex]\[ \boxed{3} \][/tex]
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.